Análise etofarmacológica do labirinto em cruz elevado aberto para avaliar comportamentos defensivos e a antinocicepção induzida pelo medo em camundongos - Sorregotti, Tatiani (Universidade Federal de São Carlos, 2013)
Exposure of rodents to an open elevated plus-maze (oEPM) elicits antinociception and increases plasma corticosterone levels. However, no studies have yet assessed the defensive behaviour repertoire of animals in this modified test situation. In Experiment 1, factor analysis was employed to characterise the behavioural profile of mice exposed to the oEPM. Experiments 2 and 3 assessed the effects of acute alprazolam (0.5-1.5 mg/kg), diazepam (0.5-1.5 mg/kg), pentylenetetrazole (10.0-30.0 mg/kg), yohimbine (0-6 mg/kg), mCPP (0-3 mg/kg), and acute and chronic fluoxetine (10.0-30.0 mg/kg) and imipramine (1.0-15.0 mg/kg) on the various behaviours identified in Experiment 1. Experiment 4 assesed the effect of nociceptive stimulus (formalin test) on behavioural profile of mice exposed to the oEPM. Experiment 5 evaluated the effects of alprazolam in mice exposed to the oEPM under noxious stimuli. The factor analyses revealed that behaviour in the oEPM can largely (77% total variance) be accounted for in terms of 3 factors: factor 1 ( depth exploration ; e.g. head-dipping on the arms), factor 2 ( cautious exploration of arms ; e.g. flatback approach), and factor 3 ( risk assessment ; stretched attend postures). Experiments 2 and 3 showed that, over the dose range used, alprazolam selectively attenuated all measures of defensiveness. Similar, though more modest, effects were seen with diazepam. Pentylenetetrazole decreased total entries and head dipping outside the central square, but did not change other behavioural measures. Although acute fluoxetine or imipramine treatment failed to modify behaviour in the oEPM, chronic fluoxetine (but not chronic imipramine) attenuated total flat back approach and increased head dipping outside the central square. While yohimbine decreased SAP frequency in the central square and flat-back total, mCPP increased the latter behaviour. Experiment 4 showed that effects of nociceptive stimulus were opposite effect of alprazolam: increased SAP in the proximal areas and arm-ends and decreased head-dipping in the arms. Experiment 5 replicated the effects observed in Experiment 2 (treatment with alprazolam per se). Together, the results indicate that the oEPM induces behavioural defensive responses that are sensitive to alprazolam and to formalin test.
Keywords: Ansiedade; Camundongos; Labirinto em cruz elevado; Mecanismo de defesa; Analgesia; Psicofarmacologia; CIENCIAS BIOLOGICAS